2013
DOI: 10.5897/ijnm2013.0099
|View full text |Cite
|
Sign up to set email alerts
|

Experience of sexual harassment and coping strategies among students of the school of nursing of a tertiary hospital in Southwest Nigeria

Abstract: This descriptive cross-sectional study documented the experience of sexual harassment (SH) and coping strategies among 250 consenting students of University College Hospital, Ibadan school of nursing, using a pre-tested questionnaire. Descriptive statistics and Chi-square test were used to analyze the data at 5% level of significance. Mean age was 23.0 ± 4.1 years, 78.8% were females and 91.2% perceived SH to be common in the school. Fifty-eight percent of respondents (20.0% males, 80.0% females) had ever been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
5
7
1
Order By: Relevance
“…This figure was within the range reported in WHO multi-county life-time prevalence of sexual partners violence among women aged 15 -49 years, (6% to 59%) [16] [17]. It was also comparable to the prevalence rate reported in a university from the same region of the country, (36.7%) [29] but studies from two other regions of the country; South-South region, (51.7% and 46.7%) [30] [31] and South West, (58%) [48] reported higher prevalence rates. Nevertheless, lower figures were reported among students from universities in Northern region of the country, (13.8% and 22.2%) [33] [34].…”
Section: Discussionsupporting
confidence: 53%
“…This figure was within the range reported in WHO multi-county life-time prevalence of sexual partners violence among women aged 15 -49 years, (6% to 59%) [16] [17]. It was also comparable to the prevalence rate reported in a university from the same region of the country, (36.7%) [29] but studies from two other regions of the country; South-South region, (51.7% and 46.7%) [30] [31] and South West, (58%) [48] reported higher prevalence rates. Nevertheless, lower figures were reported among students from universities in Northern region of the country, (13.8% and 22.2%) [33] [34].…”
Section: Discussionsupporting
confidence: 53%
“…It is also necessary to provide awareness session for the nurses who are at high risk for harassment for the recognition of the concept of harassment and what behaviors constitute harassment. This come in line with the results of Arulogun O et al (2013) (22) , and Lee S et al 2011 (11) where more than half of nursing students were exposed to harassment in the clinical training whether by touch of the patients, their relatives or other health care team members.…”
Section: Discussionsupporting
confidence: 88%
“…They may deny or minimize the experience particularly when their attacker was an acquaintance or spouse. Some may reach out for assistance, while others may withdraw (22,23) . These different reactions were reflected in the current study as less than two fifth of the female students reported confusion and fear upon harassment.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the survey conducted among selected Nigerian bank workers revealed the tolerance of distress as a ground for coping, which might further lead to workplace deviances and high attrition rate (Amazue et al, 2014). In disparity with our finding, the main coping strategies adopted by their respondents were to report to the authority (Arulogun et al, 2013). This research finding is also consistent with some previous studies which found that the culture of silence rather than speaking out is the major means of managing sexual violence within the Nigerian community (Awosusi and Ogundana, 2015;Fapohunda, 2014).…”
Section: 18supporting
confidence: 92%